37.1: Invited Paper: Using twin screw extrusion technology for the Inclusion of Phosphors with Polymers to accelerate plant growth under cover. (4th October 2019) - Tarverdi, Karnik; Fern, George R.; Marsh, Paul; Ireland, Terry; Qi, Kun; Silver, Jack
Abstract : Methods of introducing and dispersing different phosphor particles into polymers using extrusion technology are reported. The extrusion and blending of phosphor/polymer combinations containing different percentages of phosphor and subsequent film blowing was studied. The phosphor/polymer films had their light emitting properties optimised to closely match plant growth requirements. The final films performance was evaluated for horticultural applications.